COTTAGE DI KAWASAN WISATA PANTAI TELUK ARU KABUPATEN KOTABARU - Ariyanti, Winni; Agusniansyah, Nursyarif (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Teluk Aru beach is a tourist attraction that is famous for its natural beauty, culture, and local wisdom of the Mandar tribe. This is the potential and attractiveness of the Teluk Aru coast. The absence of lodging facilities and the long distance from the district center make tourists reluctant to visit. So it is necessary to have accommodation facilities in the form of lodging in accordance with the cultural characteristics of the community, traditional architecture and the natural environment. The result of the design is a cottage which is the result of exploration of the transformation of elements of traditional Mandar (Boyang) house into a modern form and appearance. So that this cottage will become an accommodation facility that can provide the embodiment of community culture, traditional architecture and natural potential. Keywords: Boyang House, Cottage, Mallasuang Manu Culture, Mandar Triblr, Teluk Aru Beach.